Post-COVID pain and quality of life in COVID-19 patients: protocol for a meta-analysis and systematic review - Yongxing Xu; Jianwen Gu; Mengrong Miao; Yitian Yang; Pule Li; Mengqi Jia; Zhaoyu Wen; Mengmeng Yu; Jiaqiang Zhang (BMJ Open)
Introduction During the COVID-19 pandemic, approximately 10%–35% of COVID-19 infected patients experience post-COVID sequela. Among these sequelae, pain symptoms should not be neglected. In addition, the sequelae of COVID-19 also decrease the quality of life of these populations. However, meta-analyses that systematically evaluated post-COVID pain are sparse.Methods and analysis A comprehensive screening will be performed by searching MEDLINE and Embase without language restriction from inception to August 2021. Cohort studies, case–control studies, cross-sectional studies and case series will be included. Case report and interventional studies will be excluded. Studies with less than 20 participants will be also excluded. We aim to investigate the prevalence of pain-related symptoms in patients after the acute phase of COVID-19. The impact of COVID-19 on the quality of life and pain symptoms among these populations in the post-acute phase will also be evaluated. ROBINS-I tool will be used to assess the risk of bias of cohort studies. The risk of bias tool developed by Hoy et al will be used to assess the risk of bias of prevalence studies. Metaprop command in Stata will be used to estimate the pooled prevalence of pain symptoms. DerSimonian and Laird random-effects models will be used to calculate the pooled relative risks. All analyses will be calculated using Stata software (V.15.0; StataCorp)Ethics and dissemination Ethics approval is not required. Results of our study will be submitted to a peer-review journal.PROSPERO registration number CRD42021272800.